Declining financial performance of local governments in Indonesia: An empirical study during Covid-19 - Karnoto, Suparjito Bin; Almasyhari, Abdul Kharis; Budiarto, Dekeng Setyo (Universitas Muhammadiyah Semarang, 2023)
This research focuses on assessing the financial performance of Regency/City Governments in Central Java Province after refocusing their budget during the COVID-19 pandemic in 2021. Budget Refocusing is a government policy to cope with the impact of the COVID-19 pandemic. This policy certainly has an impact on the financial performance of local government. The calculation process to measure the financial performance of local government using formulas adopted from the research and development section of the Ministry of Home Affairs as well as the Faculty of Social and Political Sciences, Gadjah Mada University, and applied in previous research to calculate financial ratios such as the local government fiscal decentralization, local government financial dependency, regional original income (PAD) effectiveness, and capital expenditure ratios. The results showed that 71.43% of local governments have financial capability in the less category, 62.86% in the moderate category, and 45.71% have a PAD effectiveness ratio in the very effective category. Moreover, the average capital expenditure ratio for the governments was found to be 11.47%.